Cyp2C19*2 Polymorphism Related to Clopidogrel Resistance in Patients With Coronary Heart Disease, Especially in the Asian Population: A Systematic Review and Meta-Analysis - Sun, Ying; Lu, Qing; Tao, Xuefei; Cheng, Biao; Yang, Guoxing (Frontiers in Genetics, 2020)
In recent years, the relationship between Cyp2C19*2 gene polymorphism and clopidogrel resistance reflected by platelet function assay has been studied extensively, but there is no clear conclusion yet. In order to evaluate the relationship between Cyp2C19*2 gene polymorphism and clopidogrel resistance more accurately, meta-analysis was conducted in this study. The I2 value taking 50% as the limit, the heterogeneity is judged as high or low, and then a random effect model or a fixed effect model is selected for statistical analysis.PubMed, EMBASE, Web of Science, CNKI and China Wanfang database were searched, and the related literatures from the establishment of the database to May 2020 were collected and analyzed by STATA 15.0 software. A total of 3073 patients were involved in 12 studies, including 1174 patients with clopidogrel resistance and 1899 patients with non-clopidogrel resistance. The results of this study showed that allele model (A vs. G): OR=2.42 (95%CI:1.97~2.98); dominant model (AA+GA vs. GG): OR=2.74 (95%CI:2.09~3.59); recessive model (AA vs. GA+GG): OR=4.07 (95%CI:3.06~5.41); homozygous model (AA vs. GG): OR=5.70 (95%CI:4.22~7.71); heterozygote model (GA vs. GG): OR=2.32 (95%CI:1.76~3.07), the differences were statistically significant. Also, the analysis of the Ethnicity subgroup indicated that the Asian allele model and the other four gene models were statistically significant. In conclusion,Cyp2C19*2 gene polymorphism is strongly associated with clopidogrel resistance. Allele A, genotype GA, AA and GG+GA can increase clopidogrel resistance,especially in the Asian population.